Strengthening learning during the COVID-19 pandemic with digital modules for class IV SD Negeri 1 Sindangkasih - Raden Fatia Hartini; Asep Mulyadi (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
During the COVID-19 pandemic, the Indonesian government took steps to impose restrictions on community activities that had an impact on the education sector. This has led to the re-implementation of learning activities from home which still need to be more effective. On the other hand, the difficulty in understanding learning material and the emergence of laziness in students to read the textbooks provided are problems that must be addressed immediately. One of the learning media that can be used to support learning activities at home is a learning module. Based on the results of previous research, this module is effectively used in learning in class IV SD Negeri 1 Sindangkasih. In the next stage, the module is used as material for a strengthening program for learning at home. The dedication method is strengthening the implementation of learning at home with the use of digital modules by parents of students. The results of the learning reinforcement program with digital modules are very effective for parents of students. Parents think using digital modules in learning at home is more structured and can clarify learning objectives at home. In addition to using digital modules, collaboration between teachers and parents is also a factor that needs attention to support the effectiveness of student learning activities at home.   Abstrak Pada masa pandemi COVID-19 pemerintah Indonesia mengambil langkah dengan menerapkan pemberlakuan pembatasan kegiatan masyarakat yang berdampak kepada bidang pendidikan. Hal ini menyebabkan kembali dilaksanakannya kegiatan belajar dari rumah yang dirasa belum efektif. Disisi lain, kesulitan memahami materi pembelajaran dan munculnya rasa malas pada peserta didik untuk membaca buku paket pelajaran yang diberikan menjadi permasalahan yang perlu untuk segera ditangani. Salah satu media pembelajaran yang dapat digunakan untuk mendukung kegiatan belajar di rumah adalah modul pembelajaran. Berdasarkan hasil penelitian sebelumnya bahwa modul ini efektif digunakan pada pembelajaran di kelas IV SD Negeri 1 Sindangkasih. Pada tahap selanjutnya modul tersebut digunakan sebagai bahan untuk program penguatan pembelajaran di rumah. Metode pengabdian yang digunakan adalah penguatan pelaksanaan pembelajaran di rumah dengan penggunaan modul digital oleh orangtua siswa. Hasil dari program penguatan pembelajaran dengan modul digital ini dirasa sangat efektif oleh orangtua siswa. Orangtua merasa penggunaan modul digital pada pembelajaran di rumah lebih tersusun dan dapat memperjelas tujuan pembelajaran di rumah. Selain penggunaan modul digital, kerjasama antara guru dan orangtua siswa pun menjadi salah satu faktor yang perlu diperhatikan sebagai upaya untuk mendukung efektivitas kegiatan pembelajaran siswa selama di rumah. Kata Kunci: Modul pembelajaran; pembelajaran jarak jauh; sekolah dasar